1985
DOI: 10.1271/bbb1961.49.367
|View full text |Cite
|
Sign up to set email alerts
|

Purification and some properties of a subtilisin inhibitor from adzuki beans.

Abstract: A subtilisin inhibitor was isolated from adzuki beans (Phaseolus angularis) by chromatography on CM-cellulose, Sephadex G-75, DEAE-cellulose, and SP-Sephadex C-25. The final preparation was confirmed to be homogeneous on polyacrylamide gel electrophoreses, and its pi value was 3.7. The preparation was a powerful inhibitor of microbial serine-proteinases but its activity was destroyed by trypsin and chymotrypsin. Dissociation constant of the complex of the inhibitor with subtilisin was 0.16 nM. The inhibitor wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Other inhibitors of subtilisin were sub sequently purified from cereals and legumes. Subtilisin inhibitors are found in Hordeum vulgare (barley seeds) (17,191), Vigna unguiculata (cowpea) (180), Vicia faba (broad beans) (170), Phaseolus vulgaris (black beans) (160), Phaseolus angularis (adzuki bean) (192), Vigna radiata (mung bean) (89), Cicer arietinum (chick pea) (176) and Canavalia ensiformis (jack beans) (161). These inhibitors from legumes and cereals were first characterized by their high specificities toward microbial proteinases and their relative in effectiveness against serine proteinases from animals.…”
Section: Serine Proteinase Inhibitorsmentioning
confidence: 99%
“…Other inhibitors of subtilisin were sub sequently purified from cereals and legumes. Subtilisin inhibitors are found in Hordeum vulgare (barley seeds) (17,191), Vigna unguiculata (cowpea) (180), Vicia faba (broad beans) (170), Phaseolus vulgaris (black beans) (160), Phaseolus angularis (adzuki bean) (192), Vigna radiata (mung bean) (89), Cicer arietinum (chick pea) (176) and Canavalia ensiformis (jack beans) (161). These inhibitors from legumes and cereals were first characterized by their high specificities toward microbial proteinases and their relative in effectiveness against serine proteinases from animals.…”
Section: Serine Proteinase Inhibitorsmentioning
confidence: 99%
“…Another group of related proteins from leguminous plants comprises subtilisin inhibitors from common garden bean ( Phaseolus vulgaris L.) [128], adzuki bean ( P. angularis L.) [129], broad bean ( Vicia faba L.) [22], and jack bean ( Canavalia lineata L.) [130]. In addition to subtilisin, inhibitors of leguminous plants act on other serine proteinases of microorganisms, but not trypsin.…”
Section: Properties Of Proteinase Inhibitorsmentioning
confidence: 99%
“…Although the inhibitors of this family either lack disulfides or have only one such bond per molecule, they are highly pH-stable and resistant to temperature fluctuations [121,129,136]. Moreover, it was shown that reduction of the single disulfide bond in the molecule of potato chymotrypsin inhibitor did not affect its conformation or activity [138].…”
Section: Properties Of Proteinase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adzuki Subtilisin Inhibitor (ASI), an inhibitor purified from Vigna angularis , can inhibit subtilisin with a Ki of 0.16 nM. The 10.8 kDa molecule was identified as being from the PotatoI family through amino acid sequence analysis, and was purified by CM-cellulose, Sephadex G-75, DEAE-Cellulose and Sephadex C-25 [38, 39]. Plant inhibitors do not inhibit only serine proteases, in Vigna radiate an inhibitor of aspartic protease (VrAP) of 16.6 kDa with Ki in nM range was characterized.…”
Section: Introductionmentioning
confidence: 99%